Record of egg parasitoid in Erinnyis alope (Drury, 1773) (Lepidoptera: Sphingidae) in Brazilian cassava crops - Santos, Jakeline Maria dos; Broglio, Sônia Maria Forti; Costa, Simone Silva da; Santos, José Rosildo Tenório dos (MAGISTRA, 2017)
Abstract: Parasitoids of genus Trichogramma (Hymenoptera: Trichogrammatidae) are one of the most studied groups of insects in the world because they function as biological control agents when the pest is still in the early developmental stages, eliminating it before the injury shows up. Therefore, it was investigated the occurrence of egg parasitoids of Erinnyis spp. collected during a technical visit at cassava plantations located in Fazenda Juçara, Murici, Alagoas. Samples were transported to the Centro de Ciências Agrárias, Universidade Federal de Alagoas (CECA, UFAL) in Rio Largo, AL, for observations. Caterpillars hatched from non-parasitized eggs were reared until adult emergence, when they were killed and mounted. Parasitoids that emerged from parasitized eggs were placed inside plastic microtubes with 70% alcohol. Both hosts and parasitoids were sent for identification to the Laboratory of Taxonomy, at the Departamento de Entomologia e Acarologia, ESALQ, USP, Piracicaba, SP, where the specimens were preserved in the Institution’s Museum. From the samples, Erinnyis alope (Drury, 1773) (Lepidoptera: Sphingidae) and Trichogramma marandobai Brun, Moraes & Soares, 1986 (Hymenoptera: Trichogrammatidae) were collected from cassava plantations, at Alagoas State. This is the first record of occurrence of E. alope in the State and its parasitism by T. marandobai in Brazil. Key words: Alope Sphinx Moth, Euphorbiaceae, Manihot esculenta, Trichogramma